2005
DOI: 10.1002/pbc.20574
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase C677T polymorphism: Association with risk for childhood acute lymphoblastic leukemia and response during the initial phase of chemotherapy in greek patients

Abstract: We were able to detect a statistically significant protective effect, with respect to ALL, associated with carriage of the MTHFR 677T allele [OR = 0.387 (95% CI = 0.193-0.776)]. In addition, we observed a general tendency towards lower values in all three parameters studied, associated with the MTHFR 677CC genotype, which was more evident in the transition from the induction to the consolidation phase, indicating that MTHFR genotyping may be of prognostic value in the early phase of treatment for childhood ALL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 20 publications
4
37
2
Order By: Relevance
“…The 677TT mutation decreases enzymatic activity and causes a lower rate of reduction of 5,10-MTHF to 5-MTHF, resulting in low remethylation rate of Hcy, thus increasing the Hcy level and decreasing the folate level in plasma (29,30). Therefore, this mutation may affect the levels of ALT and AST in the serum (31). However, our results showed the mutation of MTHFR C677T decreased the serum AST level (Table 2).…”
Section: Discussioncontrasting
confidence: 54%
“…The 677TT mutation decreases enzymatic activity and causes a lower rate of reduction of 5,10-MTHF to 5-MTHF, resulting in low remethylation rate of Hcy, thus increasing the Hcy level and decreasing the folate level in plasma (29,30). Therefore, this mutation may affect the levels of ALT and AST in the serum (31). However, our results showed the mutation of MTHFR C677T decreased the serum AST level (Table 2).…”
Section: Discussioncontrasting
confidence: 54%
“…1. The final search generated 13 potentially relevant studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in which the effect of MTHFR polymorphisms on the risk of both adult and childhood ALL was evaluated. Contacts to experts in the field failed to indicate the presence of any unpublished study.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of them [29][30][31][32][33][34][35][40][41][42][43][44][46][47][48][51][52][53][54][55][56]59,60,62,63,65,67,68,70,71,74 were DNA extracted from peripheral blood, bone marrow or buccal samples collected at the time of diagnosis at the study center or with unspecified patient status. Five studies included samples from remission and those collected at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies examined the relationship between Bcell ALL and risk. 30,40,41,44,64 Among the three studies 40,41,44 that looked at MTHFR C677T and risk, one study had irregularities in the genotype data presented 40 hence data from the study could not be pooled. Combining data from the other two studies showed that C677T was not significantly associated with risk (Table 2; Online Supplementary Figure S1; Online Supplementary Table S2).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation